(untitled) (Clinics, 2012)
OBJECTIVE: To determine the serum levels of interferon alpha in childhood-onset systemic lupus erythematosus patients, their first-degree relatives and healthy controls and to evaluate the associations between serum interferon alpha and disease activity, laboratory findings and treatment features. METHODS: We screened consecutive childhood-onset systemic lupus erythematosus patients in a longitudinal cohort at the pediatric rheumatology unit of the State University of Campinas between 2009 and 2010. All patients demonstrated disease onset before the age of 16. Disease status was assessed according to the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI). Interferon alpha levels were measured using an enzyme-linked immunoabsorbent assay. RESULTS: We included 57 childhood-onset systemic lupus erythematosus patients (mean age 17.33±4.50), 64 firstdegree relatives (mean age 39.95±5.66), and 57 healthy (mean age 19.30±4.97) controls. Serum interferon alpha levels were significantly increased in childhood-onset systemic lupus erythematosus patients compared to their firstdegree relatives and healthy controls. Interferon alpha levels were significantly increased in patients with positive dsDNA antibodies, patients with cutaneous vasculitis, patients with new malar rash and patients who were not receiving medication. Interferon alpha levels correlated with C3 levels and systemic lupus erythematosus Disease Activity Index scores. In addition, we observed an inverse correlation between patient age and interferon alpha levels. CONCLUSION: Interferon alpha may play a role in the pathogenesis of childhood-onset systemic lupus erythematosus, especially in cutaneous manifestations and dsDNA antibody formation. The observation that interferon alpha levels are increased in patients who are not taking medication should be investigated in longitudinal studies to determine whether elevated interferon alpha levels may predict systemic lupus erythematosus flares.